ANALISIS KETIMPANGAN PENDAPATAN DAN PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN TENGAH: PENDEKATAN HIPOTESIS KUZNETS - Laura Purnama; Alexandra Hukom (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to find out and analyze whether the Kuznets hypothesis applies in Central Kalimantan. The research method used is quantitative descriptive. Based on regression analysis and hypothesis testing, the Gross Regional Product (GR) variable does not significantly influence economic growth (PE) at the 5% significance level, but becomes significant at the 10% significance level. Overall, the regression model is not able to explain variations in economic growth well, as shown by the low R^2 value, only 1.9%. Graphical analysis also shows that the Kuznets hypothesis does not apply in Central Kalimantan in the 2017-2022 period, because there is no significant change in shape that reflects the Kuznets Curve pattern. Therefore, it can be concluded that the GR variable does not have a significant influence on economic growth in the region. This is proven by the absence of a significant inverted-U curve pattern in the relationship between these two variables. The image resulting from the analysis actually shows a relatively straight line trend and does not form a pattern as assumed in the Kuznets hypothesis. Thus, the relationship between economic growth and income inequality in Central Kalimantan in the 2017-2022 period does not follow an inverted-U pattern as hypothesized by Kuznets